An analysis of practices, contents, and purposes of faculty meetings intended as means of improving instruction in the public secondary schools in Camarines Norte - Galvante, Gloria P. 1923- (1965)
Through this study, school administrators in the Division of Camarines Norte are provided with data on existing practices regarding faculty meetings with the aim of improving classroom instruction.
Thesis (M.Ed.)--University of the Philippines
Keywords: Teaching -- Philippines -- Camarines Norte